Pengaruh Akuntabilitas, Partisipasi Masyarakat, dan Transparansi Pengelolaan Dana Desa Terhadap Kesejahteraan Masyarakat (Studi Kasus di Kecamatan Tempursari Kabupaten Lumajang) - Hidayatun Nisa; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the effect of accountability, community participation, and transparency of village fund management on community welfare. Sampling in this study using purposive sampling technique. The processed data is primary data obtained from distributing questionnaires directly and obtained 77 respondents who have met the criteria. The method used is multiple linier regression analysis with SPSS 26. The result show that accountability has no effect on community welfare, community participation has a positive effect on community welfare, and transparency in the management of village funds has no effect on community welfare in Tempursari district, Lumajang Regency.Keywords: Welfare, accountability, community participation, transparency